2002
DOI: 10.1002/jgm.281
|View full text |Cite
|
Sign up to set email alerts
|

High‐level expression of naked DNA delivered to rat liver via tail vein injection

Abstract: These results demonstrate that gene transfer into the liver via rapid tail vein injection can easily be achieved in the rat, which is more than 10 times larger than the mouse, and has significant value for gene function analysis in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
105
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(117 citation statements)
references
References 18 publications
(43 reference statements)
12
105
0
Order By: Relevance
“…Similar to the results in our previous study using pCAGGS-lacZ, 22 vIL-10 gene expression after pCAGGSvIL-10 injection was seen in the hepatocytes. Compared with the result in our previous study, the present study demonstrated a lower percentage of vIL-10-transfected cells.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Similar to the results in our previous study using pCAGGS-lacZ, 22 vIL-10 gene expression after pCAGGSvIL-10 injection was seen in the hepatocytes. Compared with the result in our previous study, the present study demonstrated a lower percentage of vIL-10-transfected cells.…”
Section: Discussionsupporting
confidence: 90%
“…As in previous reports, 20,22 we noted that transgenederived vIL-10 mRNA could also be detected in the kidney by quantitative real-time PCR. Plasmid DNA can also be delivered to the kidney via the retrograde renal vein route.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations